Profesionalisme, Sensitivitas Etika, Personal Cost Dan Intensi Melakukan Whistleblowing - Resti Yulistia M; Arie Frinola Minovia; Neva Novianti; Karina Rasaki (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
Whistleblowing in government institutions is a controversial topic regarding its impact on employees, companies and society. Although whistleblowers face a dilemma, the majority of fraud disclosures originate from employees or internal parties. The impact of professionalism, ethical sensitivity, and personal cost on whistleblowing intention is investigated in this study. The purposive sampling method was used to choose 54 tax employees from KPP Pratama Bukittinggi in West Sumatra as respondents. The result found professionalism and personal cost had an effect on whistleblowing intention, while ethical sensitivity had no effect. These findings can be used by the government and policymakers to improve professionalism in their work and boost whistleblower protection.